2016
DOI: 10.1002/jcp.25477
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute and Chronic Exercise on Skeletal Muscle Proteome

Abstract: Skeletal muscle plasticity and its adaptation to exercise is a topic that is widely discussed and investigated due to its primary role in the field of exercise performance and health promotion. Repetitive muscle contraction through exercise stimuli leads to improved cardiovascular output and the regulation of endothelial dysfunction and metabolic disorders such as insulin resistance and obesity. Considerable improvements in proteomic tools and data analysis have broth some new perspectives in the study of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 102 publications
0
42
1
Order By: Relevance
“…The HIGH group may have increased stroke volume [12], increased brain perfusion [14], and muscle adaptions that may reduce fatigue [12]. Comparatively, the LOW group lacks these chronic adaptions to exercise, which may reduce neuroplasticity induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIGH group may have increased stroke volume [12], increased brain perfusion [14], and muscle adaptions that may reduce fatigue [12]. Comparatively, the LOW group lacks these chronic adaptions to exercise, which may reduce neuroplasticity induction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, long-term exercise appears to facilitate cognitive function and memory through neuroplasticity and neuroprotective mechanisms. Additionally, regular exercise leads to chronic physiological adaptions that impact the response to a single session of aerobic exercise (see review: [12]). These adaptions include increased metabolic efficiency at a given heart rate [12], increased stroke volume [13], increased brain perfusion [14], and alterations in individual responses to stress, anxiety, and perceived rate of exertion [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some indicatory information can e.g., be retrieved from comparative studies on the differential effects of differentiated exercise (MacNeil et al, 2010; Vissing and Schjerling, 2014; Petriz et al, 2016). However, the knowledge on specific mechanotransducing mechanisms presented below (see also Figure 1), is predominantly based on findings from in vitro or animal studies.…”
Section: How Can a Mechanical Signal Elicited By Resistance Exercise mentioning
confidence: 99%
“…It also improves your appearance and delay the aging process. Moreover, physiological systems possess acute and chronic adaptations to exercise dependent on volume and intensity [34,42]. Energy for acute exercise is derived from a small amount of ATP and CP stored in muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…Increase of oxygen consumption induced by acute exercise leads to increase in the production of reactive oxygen and nitrogen species (RONS) that is associated with muscle fatigue or damage [3]. In addition, A study by Petriz et al [42] with proteomic analysis showed that protein carbonylation and enzymes related to energy metabolism were significantly reduced in the soleus muscle after the acute bout. Aerobic exercise elicits many adaptations in the involved skeletal muscles and in the metabolic and cardiorespiratory systems.…”
Section: Introductionmentioning
confidence: 99%